Light intensity and sucrose on the in vitro morpho-physiological response Selenicereus megalanthus (Haw.) Seedlings - Millones Chanamé, Carlos Eduardo (2023)
Improving the efficiency in vitro culture conditions in established yellow pitahaya micropropagation protocols, allows evaluating the dependence of sucrose in the culture medium under photoautotrophic conditions to obtain high quality seedlings in less time, which favors their acclimatization in the mass production of this species. The objective of this research was to evaluate the levels of light intensity and the use or not of sucrose in the culture medium on the in vitro morphological and physiological response of yellow pitahaya (S. megalanthus) seedlings. Vegetative sections of yellow pitahaya were placed in growth and development culture media to obtain cuttings approximately six centimeters long to obtain the explants. The containers were placed at different light intensities: 50, 100 and 150 μmol/m-2s-1, using compact fluorescent lamps, whose intensities were adjusted using a luxometer. A completely randomized design with factorial arrangement (Factor A: three light intensities and Factor B: presence and absence of sucrose in the growth and development culture medium) and seven repetitions per treatment was used. The evaluations of the morphological and physiological response were made after 45 days of in vitro culture. The traits related to water content, dry weight and shoot length allow us to explain the photoautotrophic response of yellow pitahaya seedlings grown in vitro using light intensities of 50 and 100 μmol/m-2s-1 and in the absence of sucrose.